Modern Muslim thinkers: dimensions of thought and reforms - Abdul Rahim, Adibah; Md, Yousuf Ali (Perbadanan Kota Buku, 2022)
This book provides an exposition to the life history and reform ideas of selected modern Muslim thinkers in the Muslim world from the late nineteenth to twentieth century. They are considered as the most influential and progressive thinkers of modern age due to their contributions and significant roles in the awakening of the Muslim Ummah. The authors tried to deliberate the diversity of views advocated by the thinkers in response to the challenges of modernity posed by the West ranging from religious to social, political, and educational dimensions. Each thinker has his own distinct approach in interpreting issues in Islamic thought in accordance with the context of his time and place. The authors also tried to highlight the relevance of the thinkers’ thoughts for the revitalization of contemporary Muslim ummah. By exposing the biographical background of each thinker and diversity of his thought, the readers can broaden their perspectives towards the idea of reform in Islam. In addition, this book is essential for readers to acknowledge the contributions of the modern thinkers towards the later development of Islamic thought.